Congenital ichthyosis presentation and outcome - A case series - Qudsiya A. Ansari; Vinaya A. Singh; Kailas G. Randad; Prasoon Bansal (Journal of Family Medicine and Primary Care, 2023)
The ichthyosis, also called disorders of keratinization or cornification, are heterogeneous group of disorders characterized by a generalized scaling of the skin of varying severity. The majority of ichthyosis is inherited but acquired forms can develop in the setting of malignancy, autoimmune or infectious disease, and nutritional deficiency. Autosomal recessive congenital ichthyosis, which include lamellar ichthyosis, congenital ichthyosiform erythroderma, and harlequin ichthyosis, are rare; their overall incidence has been estimated at approximately 1 in 300,000 births. In this article, we described four cases of congenital ichthyosis, their potential complications, causes of morbidity and mortality, and discussed the management and importance of genetic testing for diagnosis as definitive diagnosis is important for long-term management and counseling of the parents.